2021
DOI: 10.1084/jem.20210501
|View full text |Cite
|
Sign up to set email alerts
|

Impaired respiratory burst contributes to infections in PKCδ-deficient patients

Abstract: Patients with autosomal recessive protein kinase C δ (PKCδ) deficiency suffer from childhood-onset autoimmunity, including systemic lupus erythematosus. They also suffer from recurrent infections that overlap with those seen in patients with chronic granulomatous disease (CGD), a disease caused by defects of the phagocyte NADPH oxidase and a lack of reactive oxygen species (ROS) production. We studied an international cohort of 17 PKCδ-deficient patients and found that their EBV-B cells and monocyte-derived ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 82 publications
(218 reference statements)
0
24
0
Order By: Relevance
“…PKCδ is a serine/threonine kinase of the novel PKC sub-family and can be activated by stimulation with diacylglycerol leading to PKCδ phosphorylation and activation of downstream targets 24 . PKCδ is involved in a myriad of cellular processes involving apoptosis, proliferation, and cell survival in a variety of cell types including immune cells 24,25 . In the hematopoietic compartment, studies have shown that genetic deletion of PKCδ resulted in systemic autoimmunity which correlated with accumulation of autoreactive B cells in PKCδ knockout mice 26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PKCδ is a serine/threonine kinase of the novel PKC sub-family and can be activated by stimulation with diacylglycerol leading to PKCδ phosphorylation and activation of downstream targets 24 . PKCδ is involved in a myriad of cellular processes involving apoptosis, proliferation, and cell survival in a variety of cell types including immune cells 24,25 . In the hematopoietic compartment, studies have shown that genetic deletion of PKCδ resulted in systemic autoimmunity which correlated with accumulation of autoreactive B cells in PKCδ knockout mice 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the hematopoietic compartment, studies have shown that genetic deletion of PKCδ resulted in systemic autoimmunity which correlated with accumulation of autoreactive B cells in PKCδ knockout mice 26,27 . Similarly, patients with autosomal recessive PKCδ deficiency were severely autoimmune and suffered from systemic lupus erythematosus 25 . In myeloid cells, previous work demonstrated that loss of PKCδ resulted in a defective reactive oxygen species production and impaired extracellular trap formation in neutrophils 28 and decreased macrophage phagosomal clearance of Listeria monocytogenes and Mycobacterium tuberculosis 29,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phagocyte oxidative burst is a powerful tool for host defense against versatile pathogens such as S. aureus ( 5, 6 ). The oxidative burst can be further enhanced by priming agents, including tumor necrosis factor-α, which increase ROS production in response to secondary activating stimuli but have no effect on their own ( 28 ).…”
Section: Discussionmentioning
confidence: 99%